Redox Imbalance in Breast Cancer: From Mechanisms to Targeted Therapeutic Strategies - saad, Rusul; sahib, Ons Hussain; Jassim Dawood, Yasser; Mahdi, Montadher Ali; Abod, Kareem Salim (Asian Pacific Journal of Cancer Biology, 2026)
Breast cancer continues to be a predominant source of morbidity and mortality globally, with oxidative stress identified as a key factor in its onset, advancement, and resistance to treatment. Reactive oxygen species (ROS) drive genomic instability, induce DNA damage, and activate oncogenic signaling pathways that promote malignant transformation and tumor progression. At the same time, problems with both enzymatic and non-enzymatic antioxidant defenses speed up the disease and make treatment less effective. This review elucidates the dual role of oxidative stress in breast cancer, focusing on its influence on tumor biology and therapeutic response by analyzing key antioxidant systems-including superoxide dismutases, catalase, and glutathione peroxidases and emphasizing their adaptive upregulation during early carcinogenesis and subsequent decline as the disease progresses. Nanotechnology-based delivery systems are discussed for their ability to enhance tumor selectivity, overcome drug resistance, and minimize systemic toxicity while restoring redox balance. However, finding the best way to use these methods to get the most therapeutic benefit while causing the least amount of systemic toxicity is still a big problem. Future perspectives emphasize the necessity of identifying and clinically validating oxidative stress biomarkers to facilitate early detection, prognostication, and personalized therapeutic strategies. Additionally, a more profound comprehension of redox biology and its interaction with immune modulation is essential for the advancement of innovative and effective redox-based interventions in breast cancer management.